Olive Stone Ash as Secondary Raw Material for Fired Clay Bricks - Eliche-Quesada, D; Felipe Sesé, Manuel Ángel; Infantes-Molina, A (Advances in Materials Science and Engineering, 2017)
This work evaluates the effect of incorporation of olive stone ash, as secondary raw material, on the properties of fired clay bricks. To this end, three compositions containing 10, 20, and 30 wt% olive stone ash in a mixture of clays (30 wt% red, 30wt% yellow, and 40wt% black clay) from Spain were prepared. The raw materials, clay and olive stone ash, were characterized by means of XRD, XRF, SEM-EDS, and TG-TDA analysis. The engineering properties of the press molded specimens fired at 900 degrees C (4 h) such as linear shrinkage, bulk density, apparent porosity, water absorption, and compressive strength were evaluated. The results indicated that the incorporation of 10wt% of olive stone ash produced bricks with suitable technological properties, with values of compressive strength of 41.9MPa but with a reduced bulk density, by almost 4%. By contrast, the incorporation of 20 wt% and 30 wt% sharply increased the water absorption as a consequence of the large amount of open porosity and low mechanical strength presented by these formulations, which do not meet the standards for their use as face bricks. The bricks do not present environmental problems according to the leaching test.
Keywords: JCR; Scopus